Expression Cloning and Production of Human Heavy-Chain-Only Antibodies from Murine Transgenic Plasma Cells - Drabek, Dubravka; Janssens, Rick; de Boer, Ernie; Rademaker, Rik; Kloess, Johannes; Skehel, John; Grosveld, Frank (Frontiers in Immunology, 2016)
Several technologies have been developed to isolate human antibodies against different target antigens as a source of potential therapeutics, including hybridoma technology, phage and yeast display systems. For conventional antibodies this involves either random pairing of VH and VL domains in combinatorial display libraries, or isolation of cognate pairs of VH and VL domains from human B cells or from transgenic mice carrying human immunoglobulin loci followed by single cell sorting, single cell RT-PCR and bulk cloning of isolated natural VH-VL pairs. Heavy chain only antibodies (HCAbs) that naturally occur in camelids require only heavy immunoglobulin chain cloning. Here, we present an automatable novel, high-throughput technology, for rapid direct cloning and production of fully human HCAbs from sorted population of transgenic mouse plasma cells carrying a human HCAb locus. Utility of the technique is demonstrated by isolation of diverse sets of sequence unique, soluble, high affinity influenza A strain X-31 hemagglutinin (HA) specific HCAbs